Characteristics of the açai seed (Euterpe precatoria Martius) after thermal processing and its potential in soil-cement brick - Garcez, Lilyanne Rocha [UNESP]; dos Santos Lima, Mateus; Ribas, Luciane Farias; Balestra, Carlos Eduardo Tino; Monteiro, Nathalie Barbosa Reis; Melo Filho, João de Almeida; Gil, Miguel Angel Ramirez [UNESP] (Elsevier, 2024)
The management of the açai palm, a species of the Euterpe genus, has grown in recent years mainly for the extraction of palm heart and the pulp of the fruit called açai. After the extraction of the’ pulp, there is a significant generation of residues, as the discarded seeds account for approximately 85% of the fruit. Therefore, this research aims to characterize the açai seed after fruit processing, as well as to evaluate the potential of thermally processed seed for use in soil-cement bricks. The seed morpho-anatomy tests were performed, including moisture content, loss of ignition, ash content, thermogravimetry, fluorescence, and X-ray diffraction of the ground seeds. Tests on thermally processed seeds included readings by X-ray diffraction and laser granulometry. After evaluating the properties of the ash, it was incorporated into soil-cement mixtures in proportions of 5%, 10%, 15%, and 20%, replacing the clinker content of LC3 (Limestone Calcined Clay Cement). Based on the results obtained, soil-cement bricks were produced with a composition of 90% soil and 10% LC3, with the LC3 cement clinker being replaced by 20% açai seed ash. The results indicate the potential for the application of açai seed ash in soil-cement bricks on a practical scale, demonstrating that the ash enhances soil stabilization and increases the compressive strength of the soil-cement matrix due to its smaller particle size compared to that of the soil grains. This not only reduces the amount of cement required for the matrix but also offers environmental sustainability through the utilization of seed waste. The study underscores the potential of applying açai seed ash in the context of environmentally significant alternative technologies and sustainable practices, emphasizing the promise of the properties found in discarded açai seeds.
Keywords: Agribusiness waste; Amazon fruit; Açai seed ash; Ecologic brick; Soil-cement matrix